The role of the International Boundary and Water Commission (CILA) in water management on the United States-Mexico border, (2008-2020) - Valle Zavala, Jesús Alan (Posgrados de la División de Ciencias Económica Administrativas, 2021)
The territorial limits have been the subject of dispute for years, in the case of the border of the United States and Mexico it is no exception. It is a space that shares very similar ecosystems and natural resources in common, such is the case of water. A resource so precious that it has led to countless disputes between these two countries. With changes in population density, as well as increasing industrialization along the border, together with current technological changes, various actions have been oriented towards the search for a correct administration and processing of available border waters. The importance of this research, whose main objective is the analysis of the provisions issued by the International Boundary and Water Commission of Mexico and the United States, an institution in charge of the administration and management of binational waters. To identify whether the actions that have been carried out to date have been favorable in accordance with the current economic and social environment of the border. This research is concluded by pointing out that, although it is true that the actions carried out by both governments have been in favor of water management, they are deficient for the administration of groundwater.